(untitled) (Research, Society and Development, 2022)
The basin that makes up the tributaries of the Mogi-Guaçu and Pardo Rivers is part of the Grande River watershed, which is strictly important for the execution of various activities performed by the resident population in or near it. The release of fresh domestic sewage into the body of water and the presence of agricultural activities constitute one of the potential causes for the degradation of water resources. Objectified with this study was to analyze the water quality of the Mogi-Guaçu River through physical, chemical and microbiological parameters at different collection points, in the mining municipalities of Bom Repouso, Tocos do Moji, Inconfidente, Ouro Fino and Jacutinga. The parameters analyzed were: pH, electrical conductivity, total dissolved solids, turbidity, chemical oxygen demand, color and total coliforms. The results indicated that the values of conductivity, total dissolved solids and turbidity differed statistically following the points collected, deducing that the contamination worsens along the course of the Mogi-Guaçu River. The parameters of the Resolution of the Conselho Nacional do Meio Ambiente - CONAMA No. 357/2005 presented values within the class 2 surface water quality standard, except the true water color (75 mg. Pt Co /L) in which only the municipality of Good Rest had a satisfactory pattern.